2001
DOI: 10.2466/pms.2001.93.1.181
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of a Discrete Complex Skill Using Bernstein's Stages of Learning

Abstract: The purpose of this study was to provide quantitative data about changes in coordination after practicing a racquetball forehand drive serve. Novice women (N = 10) were videotaped before and after 10 min. of practicing a racquetball forehand drive serve on Day 1, and after 10-min. practice sessions on consecutive Days 2 through 5. The PEAK5 Motion Measurement System was used to evaluate the following dependent variables: (a) range of motion of the wrist, elbow, upper torso, and pelvis from backswing to ball co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…13,[16][17][18][19] Progress of skill acquisition involves the release of DF. 12,15 This was shown in the AMC group as their elbows became more involved in the task of two-handed catching (Table I; Fig. 1).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…13,[16][17][18][19] Progress of skill acquisition involves the release of DF. 12,15 This was shown in the AMC group as their elbows became more involved in the task of two-handed catching (Table I; Fig. 1).…”
Section: Discussionmentioning
confidence: 76%
“…Thus, across trials, children with DCD kept the individual DF of the elbow 'rigidly, spastically fixed' to solve the control problem. 12,13,15,19 Bernstein 12 also proposed that introducing temporary, rigid couplings between independent DF may reduce the computation burden on the central nervous system, because only the synergy needs active control. The data of the present study suggest that children with DCD and their AMCs also couple their limbs during a more dynamic task of catching a ball twohandedly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some evidence supporting this hypothesis is provided by a number of kinematic studies of learning tasks (McDonald et al 1989;Smith et al 2001;Vereijken et al 1992), contradictory results have been reported (Caillou et al 2002;Ko et al 2003). Moreover, experimentally, the proposed "elimination of DOFs" has typically meant a reduction in the range of joint motion (Vereijken et al 1992), in which case no DOFs are actually eliminated.…”
Section: Introductionmentioning
confidence: 99%